Effects of Different Traditional Chinese Mind–Body Exercises on Learning Abilities, Executive Functions, and Brain Connectivity in Children with Learning Difficulties - Xiaoyan Wang; Haojie Li (Behavioral Sciences)
This study examines the effects of three traditional Chinese mind–body exercises—Tai Chi (TC), Baduanjin (BD), and Health Qigong Yijinjing (YJJ)—on learning abilities, executive functions, and prefrontal brain connectivity in children with learning difficulties. Seventy-two children (aged 9–11) with learning difficulties were randomly assigned to TC, BD, YJJ, or a control group (CON). Intervention groups practiced for 12 weeks (45 min, three times per week), while the control group maintained their regular physical education. Assessments included Academic Performance Ranking (APR), Pupil Rating Scale (PRS), and executive functions. Granger causality analyses were conducted on the functional near-infrared spectroscopy data to derive the effective connectivity at the brain region levels. Post-intervention, all intervention groups showed significant improvements over the control group in PRS and APR scores (p < 0.05), with the TC group achieving higher PRS scores than the BD group. The TC group also demonstrated superior improvements in executive functions, particularly in inhibition and working memory. Additionally, the TC group exhibited significantly enhanced effective connectivity from the left and right dorsolateral prefrontal cortex to Brodmann area 8, indicating improved brain communication. Traditional Chinese mind–body exercises, particularly Tai Chi, improve academic performance, executive functions, and prefrontal cortex connectivity in children with learning difficulties. Tai Chi demonstrates superior outcomes, supporting its potential as an effective intervention for cognitive and academic development.